Synthesis and lanthanide coordination chemistry of CMPO-decorated dibenzothiophene and dibenzothiophene sulfone platforms. (14th December 2015) - Rosario-Amorin, Daniel; Ouizem, Sabrina; Dickie, Diane A.; Hay, Benjamin P.; Podair, Julien; Delmau, Laetitia H.; Paine, Robert T.
Graphical abstract: New hybrid donor ligands based on the dibenzothiophene and dibenzothiophene-5, 5-dioxide platforms decorated with C-attached carbamoylmethylphosphine oxide substituents have been prepared. The potential chelation behavior of the ligands has been explored with molecular mechanics calculations and selected coordination chemistry with Ln(NO3 )3 salts examined. The acid dependence of the solvent extraction performance of the dibenzothiophene-5, 5-dioxide derivative for Am(III) and Eu(III) has also been surveyed. Abstract: Syntheses and spectroscopic characterization data for two new hybrid chelating ligands, 4, 6-bis[(diphenyl-N, N-diethylcarbamoylmethylphosphine oxide)methyl]dibenzothiophene (2 ) and 4, 6-bis[(diphenyl-N, N-diethylcarbamoylmethylphosphine oxide)methyl]dibenzothiophene 5, 5-dioxide (3 ), that contain two CMPO fragments grafted onto dibenzothiophene and dibenzothiophene sulfone platforms, respectively, are presented. Coordination chemistry with selected lanthanide nitrates is described along with a X-ray crystal structure determination for an unexpected Eu(III) complex, Eu(4 )(NO3 )3 that contains the intermediate ligand oxidation species 4, 6-bis[(diphenyl-N, N-diethylcarbamoylmethylphosphine oxide)methyl]dibenzothiophene 5-oxide (4 ).